2018
DOI: 10.1128/iai.00042-18
|View full text |Cite
|
Sign up to set email alerts
|

Two Phytoplasmas Elicit Different Responses in the Insect Vector Euscelidius variegatus Kirschbaum

Abstract: Phytoplasmas are plant-pathogenic bacteria transmitted by hemipteran insects. The leafhopper is a natural vector of chrysanthemum yellows phytoplasma (CYp) and a laboratory vector of flavescence dorée phytoplasma (FDp). The two phytoplasmas induce different effects on this species: CYp slightly improves whereas FDp negatively affects insect fitness. To investigate the molecular bases of these different responses, transcriptome sequencing (RNA-seq) analysis of infected with either CYp or FDp was performed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 68 publications
2
27
0
Order By: Relevance
“…2A). The very high transmission efficiency of E. variegatus under natural and experimental conditions [34][35][36][37] is confirmed in our experimental system (transmission rate 100%, p = 1 27 ). Moreover, the higher vector survival rates on mutant lines (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…2A). The very high transmission efficiency of E. variegatus under natural and experimental conditions [34][35][36][37] is confirmed in our experimental system (transmission rate 100%, p = 1 27 ). Moreover, the higher vector survival rates on mutant lines (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…During RNA‐seq analysis of E. variegatus transcriptome, a fragment of the cytoplasmic actin transcript was identified. Alignment of the muscle actin fragment used as a dsRNA template with the known sequence of the cytoplasmic actin revealed that the two sequences share 82.5% identity over a 321‐bp region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, RNAi assays have not been attempted on a phytoplasma vector before the current investigation. As a first step, we took advantage of the recently published E. variegatus transcriptome assembly to perform an in silico identification of the genes coding for the major components of RNAi machinery, including Dicers, Argonauts, R2D2 and ribonuclease III enzymes. Nevertheless, the presence of all the RNAi core genes is not a guarantee of successful suppression of gene expression, because many elements strongly affect the efficiency of gene silencing in Hemiptera (reviewed by Li and colleagues).…”
Section: Discussionmentioning
confidence: 99%
“…In general, this wide range of studies has focused on annotating immune pathways in species (often of agriculture importance) without high quality genomes (e.g., [62,63]), elucidation of hostpathogen interactions of ecological interest (e.g., [38,[64][65][66]), and characterization of pathogen-vector interactions of medical relevance (e.g., [67,68]). There has been relatively less focus on explicitly comparative studies, either comparing multiple pathogens in the same species, or comparative studies across species, albeit with a few exceptions (e.g., [38,55,[69][70][71][72][73][74]).…”
Section: Complexity Of the Transcriptional Response To Infectionmentioning
confidence: 99%